Effects of the cognitive-behavioral You Can Do It! Education program on the resilience of Japanese elementary school students: A preliminary investigation. (2017) - Yamamoto, Toshie; Matsumoto, Yuki; Bernard, Michael E.
Highlights: The You Can Do It! Education (YCDI) helped boost children's resilience. YCDI group resilience differed significantly at post-test from the control group's. The YCDI group also showed greater awareness of support resources. Abstract: The effect of a mental health promotion program based on cognitive behavioral therapy and social-emotional learning called "You Can Do It! Education" on the resilience of elementary school students was evaluated. Participants were fourth grade students at elementary schools in the Tokyo Metropolitan Area, who were assigned to the intervention ( n  = 78) or control ( n  = 47) group. The intervention group was taught eight program lessons by a visiting counselor, which covered topics related to resilience and the relationships of thinking, feeling, and behaving. The intervention group showed significant improvements in resilience and social support, whereas the control group did not. We discuss the program's feasibility for enhancing resilience and its limitations in Japanese school settings.